Business performance improvement through cost management - Ojo, Ade T.; Faculty of Business Administration, University of Lagos (Lagos : University of Lagos Press, 1992)
The book brings together a group of papers presented at the Second National Biennial Conference, organized by the faculty of Business Administration, University of Lagos, with the theme, 'Improving Business Performance through Cost Management '.
Includes bibliographical references and index.
ucj 16/01/2019
Loans
Keywords: Business enterprises--Finance.